2018
DOI: 10.1080/13607863.2018.1453483
|View full text |Cite
|
Sign up to set email alerts
|

Mental health knowledge and training needs among direct care workers: a mixed methods study

Abstract: Data from this study suggest important areas for DCW development. However, system issues that affect DCWs such as workload, resources, mental health stigma, and diverse client populations should be addressed concurrently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…The knowledge gaps among PCAs identified in the present study are largely congruent with reports from previous studies, which have consistently reported that direct care workers lacked a comprehensive understanding of the symptoms of depression and tended to view depression as dispositional problems (Ayalon et al, 2008;Davison et al, 2009;Gleason & Coyle, 2016;Konnert et al, 2018;McCabe et al, 2008). Compared with other LTSS staff such as social workers, nurses, and case managers, direct care workers tended to hold less accurate beliefs about symptoms of depression and were less familiar with the effectiveness of depression treatments (Ayalon et al, 2008), possibly due to a lower level of education.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The knowledge gaps among PCAs identified in the present study are largely congruent with reports from previous studies, which have consistently reported that direct care workers lacked a comprehensive understanding of the symptoms of depression and tended to view depression as dispositional problems (Ayalon et al, 2008;Davison et al, 2009;Gleason & Coyle, 2016;Konnert et al, 2018;McCabe et al, 2008). Compared with other LTSS staff such as social workers, nurses, and case managers, direct care workers tended to hold less accurate beliefs about symptoms of depression and were less familiar with the effectiveness of depression treatments (Ayalon et al, 2008), possibly due to a lower level of education.…”
Section: Discussionsupporting
confidence: 89%
“…PCAs' relevant work experiences averaged 6.3 years in our study sample which could explain their enhanced performance on the knowledge quiz in comparison to community adults. Interestingly, 72% of PCAs in our study disagreed or strongly disagreed with the statement that depression is a natural part of being old whereas normalization of depression in later life was a prevalent misconception among direct care workers from previous studies (Ayalon et al, 2008;Davison et al, 2009;Konnert et al, 2018).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations